MSME Internationalization Strategy Towards Global Business Competition Case Study on CV. Dua Putri Sholehah “HUNAY” Probolinggo - Joni Hendra; Sudarmiatin Sudarmiatin; Rosmiza Bidin (Pusat Riset dan Inovasi Nasional, 2024)
In the Indonesian economy, Micro, Small and Medium Enterprises are the business group that has the largest number and has proven to be resistant to various shocks from the economic crisis. MSMEs are encouraged to be able to expand to the global market, not just on a national scale. Strategy is very important to determine the company's success in achieving its long-term goals. By choosing the right strategy for a particular company position, a company will have a competitive advantage. The aim of this research is to find out what is the most appropriate strategy for CV. Dua Putri Sholehah